Simulation of High Viscosity Gas-Liquid Two-Phase Flow in a Horizontal Mini Pipe - Sukamta Sukamta (Semesta Teknika, 2019)
Two-phase flow is used in many industries such as nuclear reactors, boilers, condensers, liquefactions of natural gas, etc. Two-phase flow is a flow in a pipe which has two states of fluid such as solid-liquid, liquid-gas, gas-solid. In a two-phase flow, there are three channels, namely vertical, horizontal and inclined channels. In the horizontal channel, the most widely found flow is the flow patterns of stratified flow, bubble flow, plug flow, stratified wavy flow, annular flow, and slug flow. Refer to the previous research above, the flow patterns were mostly obtained by using an experimental study. The advantage of using the simulation is the ability to predict the flow pattern and pressure gradient before doing the experimental study so it can be known earlier if it will have an insecure flow pattern, i.e. slug flow. This research was conducted to find the flow pattern and pressure gradient by using a Computational Fluid Dynamics (CFD) software, the Ansys Fluent 19.0 Student. The model which was used is the Volume of Fluid (VOF) with the fluid of air-water and glycerin (40%-70%). The length of the pipe was 200 mm, the inner diameter was 1.6 mm, and the length of the test section was 100 mm. Liquid superficial speeds (JL) of 0.033 m/s; 0.149 m/s; 0.232 m/s; 0.539 m/s; 0.7 m/s; 2.297 m/s and 4.935 m/s were used, while the air superficial speed (JG) was 9.62 m/s. The result of the simulation showed slug annular and churn flow patterns. Slug annular was formed at JL= 0.033 m/s; 0.149 m/s and 0.232 m/s with the glycerin content of 40% and 50%. Slug annular pattern was formed when the glycerin content was 60% and 70% with JL= 0.539 m/s. Viscosity affects the flow pattern, the higher the glycerin content, the higher the viscosity and the more fluid than air. The higher the JL and glycerin content, the higher the pressure gradient.